2011
DOI: 10.1186/1476-069x-10-73
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to arsenic in drinking water is associated with increased prevalence of diabetes: a cross-sectional study in the Zimapán and Lagunera regions in Mexico

Abstract: BackgroundHuman exposures to inorganic arsenic (iAs) have been linked to an increased risk of diabetes mellitus. Recent laboratory studies showed that methylated trivalent metabolites of iAs may play key roles in the diabetogenic effects of iAs. Our study examined associations between chronic exposure to iAs in drinking water, metabolism of iAs, and prevalence of diabetes in arsenicosis-endemic areas of Mexico.MethodsWe used fasting blood glucose (FBG), fasting plasma insulin (FPI), oral glucose tolerance test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
139
5
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(152 citation statements)
references
References 34 publications
6
139
5
2
Order By: Relevance
“…Second, our results were likely to be affected by some misclassification of T2DM. Because the validity of glucometer has been a concern,33 34 inaccurate results might result from the use of a glucometer when measuring fasting plasma glucose levels in several studies 11 15 30. Third, although significant increased risk of T2DM associated with iAs >250 µg/L was found in the dose–response analysis, the observed threshold effect might arise from an effect of limited power, and no threshold effect would be found if infinite sample size was included.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our results were likely to be affected by some misclassification of T2DM. Because the validity of glucometer has been a concern,33 34 inaccurate results might result from the use of a glucometer when measuring fasting plasma glucose levels in several studies 11 15 30. Third, although significant increased risk of T2DM associated with iAs >250 µg/L was found in the dose–response analysis, the observed threshold effect might arise from an effect of limited power, and no threshold effect would be found if infinite sample size was included.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the evidence describing the association with arsenic exposure and prevalence of diabetes came from community-based studies in Taiwan and Bangladesh, where people were exposed to drinking water contaminated with arsenic. [1][2][3][4] More recently, evidence from the United States, Mexico and Canada have supported this association, [5][6][7][8][9] and a recent meta-analysis found that every 100 mcg/L increment of iAs in drinking water was associated with a 13% increase in the incidence of diabetes. [18] Additionally, there is emerging evidence that arsenic metabolism, as opposed to iAs exposure alone, may play a role in the diabetogenic effects of arsenic.…”
Section: Discussionmentioning
confidence: 95%
“…While the majority of the literature surrounding arsenic-induced DM has involved areas in Taiwan and Bangladesh where the arsenic content of drinking water is high, [1][2][3][4] there have been several other population-based studies in North America that have shown a similar association. [5][6][7][8][9] Here, we present a case of newlydiagnosed DM that was thought to be secondary to chronic arsenic exposure.…”
Section: Introductionmentioning
confidence: 99%
“…A ubiquitous metalloid element, As is of particular interest to ecotoxicologists and the general public because of its toxicity to biota and risks for human health (Rahman et al 2012;Meharg et al 2014). Studies have reported the adverse effects on humans living near gold ore mines from exposure to inorganic As, such as marked increases in the number of cases of hypertension, diabetes and cancer (del Razo et al 2011;Colín-Torres et al 2014).…”
Section: Introductionmentioning
confidence: 99%